Role of thyroid dysfunction in long-term psychological prognosis of sepsis - Zhao, Enfang; Hu, Chunhua; Jia, Wenqing; Zhang, Tingyuan; Shao, Huanzhang (Frontiers in Psychiatry, 2025)
BackgroundAfter recovery from sepsis, approximately 10%-50% of patients develop long-term psychological complications such as anxiety, depression, and post-traumatic stress disorder, yet predictive indicators for these complications remain unclear. Emerging evidence suggests that thyroid function may hold prognostic value for sepsis itself. Building on this evidence, the present study aims to investigate the impact of baseline peripheral thyroid indicators on long-term psychological outcomes (within 28 weeks) in sepsis patients.MethodsA consecutive sample of 814 sepsis patients was included. Baseline data including demographic characteristics, thyroid function indices, and peripheral inflammatory markers were collected, and psychological outcomes within 28 weeks of follow-up (i.e., anxiety, depression, and post-traumatic stress disorder) were evaluated. ROC analysis, Kaplan-Meier survival analysis, and multivariate COX regression were employed for analysis.Results(1) Higher levels of peripheral TT3, FT3, TT4, and FT4 at baseline were correlated with a reduced risk of poor psychological outcomes within 28 weeks. Sepsis-induced hypothyroidism was associated with an increased risk of poor psychological outcomes within 28 weeks. (2) These associations appeared to be more pronounced in elderly patients. (3) Peripheral TSH levels showed no such predictive value; similarly, “low-normal thyroid function” (defined as relatively high peripheral TSH within the normal range) also lacked predictive value. (4) A negative monotonic relationship was observed between baseline peripheral thyroid hormones and peripheral levels of tumor necrosis factor-α, interleukin-6, and interleukin-8.ConclusionDiminished thyroid function may be associated with relatively poor long-term psychological outcomes (within 28 weeks) in sepsis patients, possibly more so in the elderly. Given the observed association between thyroid hormones and peripheral inflammatory factors, this potential prognostic relationship may be partially mediated by inflammatory mechanisms. However, this remains a preliminary speculation and requires further validation.